2011
DOI: 10.1111/j.1540-8175.2011.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Torsion and Untwisting: Further Insights into Mechanics and Timing Interdependence: A Viewpoint

Abstract: Ventricular torsion and untwisting are essential for normal ventricular function and their mechanisms are related to the temporal responses of the helical and circular muscle fibers that comprise cardiac architecture. Explanation of the presystolic isovolumic contraction (IVC) period is essential for analysis of these interactions. Structural and imaging studies by magnetic resonance, speckle tracking, velocity vector encoding, and sonomicrometer crystals are described to define why and how different muscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 76 publications
(244 reference statements)
3
104
0
1
Order By: Relevance
“…5 ). These rotational parameters add important information on myocardial performance [63] . The twisting motion of the LV is aided by the helical arrangement of the subepicardial (left handed) and subendocardial (right handed) fibres [7] .…”
Section: Rotational Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). These rotational parameters add important information on myocardial performance [63] . The twisting motion of the LV is aided by the helical arrangement of the subepicardial (left handed) and subendocardial (right handed) fibres [7] .…”
Section: Rotational Mechanicsmentioning
confidence: 99%
“…Similarly, in the preterm neonatal population, increased afterload appears to negatively impact those measurements [65] . Rotational mechanics can be assessed by STE in a similar fashion to the method described above and demonstrates acceptable agreement with twist measured by magnetic resonance imaging (MRI) [63,66] . Twist as a marker of cardiac function has been validated in adults and children [45,67] .…”
Section: Rotational Mechanicsmentioning
confidence: 99%
“…Кони-ческая форма верхушки ЛЖ необходима для обеспе-чения нормальной сократительной функции сердца. При ишемическом повреждении геометрия ЛЖ изме-няется в результате переориентации косых волокон верхушки в более горизонтальное положение, что приводит к снижению торсионного движения вер-хушки и впоследствии к ухудшению систолической функции ЛЖ [12,27,28].…”
Section: результаты модифицированной левожелудочковой реконструкции сunclassified
“…However, myocardial untwist also occurs preejection, and an understanding of IC is said to be essential to explain this systolic-diastolic interaction. 20 Luo et al found that in patients with systolic HF, myocardial untwist during IC is prolonged into the ejection phase and that torsion during ejection is also prolonged into the diastolic phase. 23 Cho et al also reported that the ability of the IVV and IVA to predict the exercise capacity of patients with depressed systolic function might be explained by dynamic changes of IC that affect the force of cardiac contraction during ejection, and the timing of systolic cross-over into diastole.…”
Section: Systolic and Diastolic Interaction And The Role Of Isovolumementioning
confidence: 99%